Optimal risk computation on precious metal’s assets diversification - Jayeola, Dare; Sufahani, Suliadi; Ismail, Zuhaimy; Ahmad, Wan; Nor, Maria; Ismoen, Muhaimin; Maselan, Norafiz (International Journal of Engineering and Technology, 2018)
Optimization is the selection of a best element with regards to certain criterion from set of available alternatives. This paper investigates the effects of assets in optimizing risk using diversification strategy and also examines gold quality of hedging and safe haven. The reduction strength of assets is estimated. Hence, it is observed that gold exhibits highest risk reduction strength. Also it is noticed that gold acts as hedge and safe haven for investors during economic recession.